[PP.32.03] CLINICAL CHARACTERISTICS AND BLOOD PRESSURE BEHAVIOR OF PATIENTS YOUNGER THAN 30 YEARS WITH APPARENT HYPERTENSION. (September 2016) - Kasiakogias, A.; Konstantinidis, D.; Tsioufis, C.; Dimitriadis, K.; Kintis, K.; Kalos, A.; Nikolakopoulos, E.; Bazoukis, G.; Chatzis, D.; Kallikazaros, I.; Tousoulis, D.
Abstract : Objective: Rates of hypertension (HT) increase with advancing age, but there is little data about young hypertensive patients. We investigated clinical, blood pressure (BP) and laboratory data of adults less than 30 years of age visiting a specialized HT unit. Design and method: We studied 139 individuals aged 18–30 years that visited our clinic for evaluation of high BP. Clinical history and demographics were collected and 24-hour BP monitoring, echocardiography and routine blood testing was performed in all participants. Further testing for secondary causes of HT was run where appropriate. Based on uncontrolled office BP (>140/90mmHg) and ambulatory BP (>130/80mmHg), participants with sustained HT, white-coat HT, masked HT and normal BP were identified. A fall of BP by <10% at night-time was defined as non-dipping. Left ventricular hypertrophy was defined as a left ventricular mass index greater than 115gr/m 2 for men and 95gr/m 2 for women. Results: Participants had a mean age of 23 ± 5 years and were mostly male (80%). Prevalence of a BMI over 30Kg/m 2 and abdominal obesity was 30% and 31% respectively, while 37% of patients were smokers. A family history of HT was reported by 38% of participants. Mean office systolic/diastolic BP was 139 ± 17/87 ± 13mmHg and mean ambulatory BP was 129 ± 13/76 ± 11mmHg. Fourteen patients (10%) were under antihypertensive treatment and 8 patients (5.8%) were diagnosed with a secondary cause of HT. Out of the untreated patients, 39 patients (31%) had sustained HT, 36 patients (29%) had white-coat HT, 15 patients (12%) had masked HT and 35 individuals (28%) were normotensive. Prevalence of non-dipping was 52%. Left ventricular mass index was 75 ± 16 gr/m 2 and only 2% of patients had left ventricular hypertrophy. Conclusions: Young adults visiting a specialized HT unit have multiple risk factors and are often non-dippers, while secondary HT remains a rare cause. Ambulatory BP monitoring is important for the diagnosis of sustained HT in such a population.